The age effect in evaluation of hearing aid benefits by speech audiometry - Mueller, A.; Hocke, T.; Hoppe, Ulrich; Mir-Salim, P. (HNO, 2016)
BACKGROUND AND AIM: Hearing loss is one of the most common disabilities in the elderly. The aim of this study was to investigate the relationship between pure-tone hearing loss and maximum monosyllabic perception and speech perception with hearing aids. The focus of the investigation was elderly patients. MATERIALS AND METHODS: In this prospective study, 188 patients with sensorineural hearing loss were included. The pure-tone audiogram (4FPTA), the Freiburg speech intelligibility test with headphones and the word recognition score with hearing aids at 65 dB SPL were measured and evaluated. RESULTS: An increasing age was associated with higher discrepancy between the maximum speech perception and speech understanding with hearing aids. The mean difference between maximum monosyllabic perception and speech perception with hearing aids is about 20% in the elderly population. CONCLUSION: The intended goal of hearing aid prescription, the match between maximum monosyllabic perception and word recognition score with hearing aids within 5 to 10%, is not achieved in the elderly population.
EVALuna2:33934